Fretting fatigue tests on shrink-fit specimens and investigations into the strength enhancement induced by deep rolling. (December 2015) - Bertini, L.; Santus, C.
Highlights: Shrink-fit fretting fatigue tests with round geometry and bending cyclic loading. Experimental evidence of the enhancement effect produced by deep rolling. Crack arrest approach not adequate especially for deep rolled closed cracks. Shallow crack initiation evidence and correlation to the shear stress amplitude. Prediction with a multiaxial critical plane fatigue model based on shear stress. Abstract: The shrink-fit connection undergoes fretting fatigue at the edge of the contact, where both stress concentration and micro-slip take place. A fretting test set-up with a round-shaped specimen is proposed that eliminates lateral edge contact and misalignment, and is also appropriate for deep rolling. Comparative experiments showed a notable strength improvement, induced by deep rolling, along with the beneficial effect of friction reduction due to lubrication. Multiple cracks with clear shallow paths were evident after SEM observation, thus the maximum shear stress amplitude was assumed as a correlating parameter, while the crack arrest was inappropriate especially for deep rolled specimens.